A high energy density asymmetric supercapacitor from ultrathin manganese molybdate nanosheets. (1st September 2016) - Mu, Xuemei; Zhang, Yaxiong; Wang, Huan; Huang, Baoyu; Sun, Pengbo; Chen, Tao; Zhou, Jinyuan; Xie, Erqing; Zhang, Zhenxing
Abstract : Graphical abstract: The assembled MnMoO4 ·nH2 O//AC aqueous asymmetric supercapacitor present an energy density of 31.6 Wh kg −1 at a power density of 935 W kg −1 and considerable cycling stability. Abstract : Highlights: MnMoO4 ·nH2 O nanosheets on nickel foam is used as binder-free electrode. The electrode deliveres high specific capacitance and significant stability. MnMoO4 ·nH2 O//AC supercapacitors perform high energy density. Abstract: Manganese molybdate is highly significant to improve its energy density to meet the application requirement of hybrid vehicles and renewable energy systems. Here, we report a binder-free ultrathin manganese molybdate (MnMoO4 ·nH2 O) nanosheets/nickel foam electrode for high energy density asymmetric supercapacitor by a facile one-step hydrothermal method. This binder-free electrode demonstrates a very high specific capacitance of 1271 F g −1 at a scan rate of 5 mV s −1 . After 2000 charge/discharge cycles, 84.5% of the initial specific capacitance (945.6 F g −1 ) is still maintained. Further SEM, TEM and XPS results suggest that this performance degradation can be ascribed to the mechanical expansion of MnMoO4 during the ion insertion/removal process or the dissolution of some MnMoO4 during the charge/discharge cycles. An aqueous asymmetric supercapacitor using the MnMoO4 ·nH2 O as the cathode with an activated carbon anode can deliver an energy density of 31.6 Wh kg −1 at a power density of 935 W kg −1 . The remarkable performance of binder-free MnMoO4 ·nH2 O on Ni foam suggest their potential use as positive electrode material for high performance supercapacitors.